2017
DOI: 10.1038/nature22394
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the activated GLP-1 receptor in complex with a G protein

Abstract: Summary Glucagon-like peptide-1 (GLP-1) is a hormone with essential roles in regulating insulin secretion, carbohydrate metabolism and appetite. GLP-1 effects are mediated through binding to GLP-1R, a family B G protein-coupled receptor (GPCR) signaling primarily through the stimulatory G protein Gs. Family B GPCRs are important therapeutic targets, however our understanding of their mechanism of action is limited by the lack of structural information on activated and full-length receptors. Here we show the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
568
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 503 publications
(642 citation statements)
references
References 58 publications
35
568
1
4
Order By: Relevance
“…Crystal structures have also been determined for ternary signaling complexes, such as that of β 2 AR with agonist and hetereotrimeric G protein (R*GL) (Rasmussen et al, 2011b) and rhodopsin with arrestin (R*AL) (Kang et al, 2015) (Fig 3). Recent cryo-EM structures of R*GL states (Liang et al, 2017; Zhang et al, 2017) have confirmed some of the key features of the β 2 AR—G protein complex. Finally, although not associated with a high resolution structure, a recent report indicates that under some circumstances a ‘megaplex’ of GPCR, heterotrimeric G protein and arrestin may exist as a functioning signaling entity (Thomsen et al, 2016) mediating endosomally-based GPCR signaling.…”
Section: Towards a Structure-based Understanding Of Gpcr-ligand Pharmmentioning
confidence: 86%
“…Crystal structures have also been determined for ternary signaling complexes, such as that of β 2 AR with agonist and hetereotrimeric G protein (R*GL) (Rasmussen et al, 2011b) and rhodopsin with arrestin (R*AL) (Kang et al, 2015) (Fig 3). Recent cryo-EM structures of R*GL states (Liang et al, 2017; Zhang et al, 2017) have confirmed some of the key features of the β 2 AR—G protein complex. Finally, although not associated with a high resolution structure, a recent report indicates that under some circumstances a ‘megaplex’ of GPCR, heterotrimeric G protein and arrestin may exist as a functioning signaling entity (Thomsen et al, 2016) mediating endosomally-based GPCR signaling.…”
Section: Towards a Structure-based Understanding Of Gpcr-ligand Pharmmentioning
confidence: 86%
“…The new, potent α/β-peptide agonists should be useful for refining models of the PTHR1 in the activated state. 2527 …”
Section: Discussionmentioning
confidence: 99%
“…However, the degree of this interdomain opening, when it can be observed, varies for different complexes from relatively small movements or rotations up to a maximum of a 127°rotation in the crystal structure of ␤ 2 AR-G S . CryoEM studies of the ␤ 2 AR-G S complex and low resolution images of the CTR-G S complex further indicate the helical domain can occupy multiple conformations and has a high degree of mobility (4, 8 (1,4,5). However, early low resolution structures of the rhodopsin-G T complex indicated a 2:1 stoichiometry, suggesting the dimeric receptor was the minimal functional unit for G T activation (3).…”
Section: G Protein-coupled Receptors (Gpcrs)mentioning
confidence: 99%
“…Although rhodopsin was the first GPCR crystal structure to be solved in 2000 (3), issues with expression of the receptor in heterologous systems and stabilization of rhodopsin-G T hampered efforts to crystallize the complex, and the 2011 report was at relatively low resolution. It was not until June 2017 that additional higher resolution structures of GPCR-G protein complexes of two class B GPCRs emerged (4,5). The structures of calcitonin receptor (CTR) and glucagonlike peptide 1 receptor (GLP-1R) with G S were solved by cryoelectron microscopy (cryoEM) using tagged and/or truncated receptors expressed and purified from insect cells.…”
Section: G Protein-coupled Receptors (Gpcrs)mentioning
confidence: 99%